Penurunan Intensitas Dismenore dengan Akupresur Pada Titik Zusanli (St 36) SMP Tahfidh Al Hidayah - Sumarni, Sumarni; Aulia, Awit; Restiana, Erina Dwi; Dewi, Kumala Sari (JURNAL KESEHATAN TERAPAN, 2024)
Dysmenorrhea or menstrual pain are cramps in the lower abdomen which sometimes spread to the lower back and thighs, generally complained by some women before menstruation which can last 2-3 days. One of the problems that teenagers often experience during menstruation is menstrual pain. Dysminorrhea can be treated by administering pharmacological therapy with non-steroidal anti-inflammatory drugs and non-pharmacological therapy with acupressure techniques. administering Zusanli point acupressure (ST36) is effective in reducing dysmenorrhea in adolescents. The aim of this study was to determine the effect of administering Zusanli point (ST36) acupressure on menstrual pain among female adolescents at Tahfidh Al HIdayah Middle School. Method: The research used was quasi-experimental with a one group pretest-posttest approach. The sample in this study was 30 young women who were experiencing dysmenorrhea on the first day of menstruation at Tahfidh Al Hidayah Middle School. Results: The average pain scale for menstrual pain/dysminorrhea before the acupressure intervention at the Zusanli point or ST36 point was 8.83, while the average pain scale for menstrual pain/dysminorrhea after the intervention was 3.433. There is a significant effect of acupressure therapy at the Zusanli point (ST 36) on menstrual pain/dysminorrhea in young women with a value of p: 0.000 (p<0.005) with a strong correlation level (0.818). Conclusion: There is a strong correlation of acupressure therapy at the Zusanli point (ST 36) on menstrual pain/dysminorrhea in young women. Suggestion: There is a need to increase knowledge and education on the management of dysmenorrhea using non-pharmacological methods, namely acupressure at the Zusanli point (ST36) to reduce complaints of menstrual pain/dysmenorrhea in young women.